Latent profiles of spiritual care competence among Chinese nursing undergraduates: Correlations with spiritual care cognition and meaning of life - Yang Guo; Ruonan Wang; Anqi Li; Jie Yao; Lingkun Wang (PLoS ONE, 2026)
Background Spiritual care occupies a special position in overall care and improving the quality of services provided to patients. However, China’s higher nursing education is still in its infancy. The purpose of this research is to explore the heterogeneity of spiritual care competence of undergraduate nursing students in China. Methods A multicenter cross-sectional design was employed. From July 2024 to February 2025, a convenience sample of 1,224 undergraduate nursing students was recruited from four nursing colleges in the Guanzhong region of Shaanxi Province, China. Data were collected using the Chinese versions of the Spiritual Care Competence Scale, the Spiritual Care Cognition Scale, and the Meaning in Life Questionnaire. Descriptive and correlational analyses were performed using SPSS version 27.0, while latent profile analysis and ordinal logistic regression were conducted using Mplus version 8.0. Results The mean total score for spiritual care competence was 77.61 ± 14.61. Latent profile analysis identified three distinct profiles: a low-competence group (47.1%, 62.3 ± 8.2), a moderate-competence group (42.1%, 79.6 ± 6.7), and a high-competence group (10.8%, 95.1 ± 7.9). The model demonstrated high classification accuracy, with an entropy value of 0.948, and the Lo–Mendell–Rubin likelihood ratio test (LMRT) was significant (p = 0.006). Spiritual care competence was significantly positively correlated with spiritual care cognition (r = 0.540) and sense of meaning in life (r = 0.479) (both p < 0.01). Ordinal logistic regression indicated that lack of clinical internship experience, distant teacher–student relationships, absence of humanistic care education, lower levels of spiritual care cognition, and lower sense of meaning in life were key predictors of membership in lower competence profiles. Conclusion The spiritual care competence of undergraduate nursing students in China is underdeveloped and urgently needs to be improved. Their potential profiles can be divided into three categories, namely C1-low spiritual care competence, C2-medium spiritual care competence and C3-high spiritual care competence. Clinical internships, effective teacher–student mentoring, humanistic education, as well as individual spiritual cognition and sense of meaning in life, are key facilitators of competence development. It is recommended to integrate structured spiritual care training into undergraduate nursing curricula and to establish a systematic mentorship program.